Synthesis, characterization and biological evaluation of ruthenium(II) complexes [Ru(dtzp)(dppz)Cl]+ and [Ru(dtzp)(dppz)CH3CN]2+ for photodynamic therapy. (January 2017) - Yu, Hui-juan; Liu, Jiang-ping; Hao, Zhi-feng; He, Jun; Sun, Ming; Hu, Sheng; Yu, Lin; Chao, Hui
Abstract: Two new Ru(II) complexes [Ru(dtzp)(dppz)Cl] + 1 and [Ru(dtzp)(dppz)CH3 CN] 2+ 2 (dtzp = 2, 6-di(thiazo1-2-yl)pyridine; dppz = dipyrido[3, 2- a :2′, 3′- c ]phenazine) have been synthesized and evaluated as photodynamic anticancer agents. The results of the spectra titration, thermal denaturation and electrophoresis experiments suggest that both complexes could intercalatively bind to DNA and photocleave DNA efficiently by ROS generation and photoinduced electron transfer. When incubated under visible light (470 nm), complex1 and2 generate great photocytoxicity towards Hela cells in both 2D cancer cell monolayer and 3D MCTS cancer models, and a much greater photocytotoxicity was observed for complex1, which may be associate with its' larger cellular uptake efficiency and stronger absorption at 470 nm. Flow cytometry analysis and immunofluorescence assay revealed that complex1 inhibited Hela cell proliferation through G2M phase cycle arrest and cell apoptosis and could generate great photodamage to chromatin DNA. Complex1 may be a prominent PDT candidate used for treating cervical carcinoma. Highlights: Two new ruthenium complexes have been synthesized and characterized. Complex1 shows great photocytotoxicity towards Hela cells (IC50 = 1.9 μM). Complex1 inhibits Hela cell proliferation by induction of G2 M phase cycle arrest and cells apoptosis.